EXPLORING SOCIAL WORK : An Anthropological Perspective - Bell, Linda, author 632727 (Bristol, UK : Policy Press, 2020)
Providing a reflexive anthropological account of social work, this original book widens our insights into the multi-faceted identity of social workers and different cultures of social work, offering an array of thought-provoking international insights into how social work practitioners view society, how their world views can affect their practice and how wider society views them. Considering the growing influence of clinical science and cultural representations of their work, Bell critically examines the changes and challenges in social workers’ preoccupations and contributions to society. Going to the heart of identities and definitions in social work, this book is refreshing reading for academics, researchers, students and practitioners alike.